Modeling and Optimal Control of Batch Processes Using Recurrent Neuro-Fuzzy Networks. - Zhang, J. (IEEE Transactions on fuzzy systems)
A recurrent neuro-fuzzy network based strategy for batch process modeling and optimal control is presented in this paper. The recurrent neuro-fuzzy network allows the construction of a ?global? nonlinear long-range prediction model from the fuzzy conjunction of a number of ?local? linear dynamic models. In this recurrent neuro-fuzzy network, the network output is fed back to the network input through one or more time delay units. This particular structure ensures that predictions from a recurrent neuro-fuzzy network are long-range or multi-step-ahead predictions. Long-range predictions are particularly important for batch processes where the interest lies in the product quality and quantity at the end of a batch. To enhance batch process control and monitoring, a model capable of predicting accurately the product quality/quantity at the end of a batch is required. Process knowledge is used to initially partition the process nonlinear characteristics into several local operating regions and to aid in the initialization of the corresponding network weights. Process input output data is then used to train the network. Membership functions of the local regimes are identified and local models are discovered through network training. An advantage of this recurrent neuro-fuzzy network model is that it is easy to interpret. This helps process operators in understanding the process characteristics. The proposed technique is applied to the modeling and optimal control of a fed-batch reactor.